Framework dan Code Generator Pengembangan Aplikasi Android dengan Menerapkan Prinsip Clean Architecture - Aflah Taqiu Sondha; Umi Sa’adah; Fadilah Fahrul Hardiansyah; Maulidan Bagus Afridian Rasyid (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2020)
Android is one of smartphone operating systems that has highest market share in Indonesia. Due to its high market share, Android developers must develop Android applications faster and produce maintainable code. Unfortunately, the existing Android development system is not effective because of its dependency on the developer's experiences and pieces of knowledge that differ from each other. Therefore, there must be a new Android development model to produce maintainable code that implements clean architecture principles code with shorter time development. This system produces a code generator in Android Studio's template plugin that will generate a framework of the Android project with MVP architecture and implements clean architecture inside that framework. This generated framework is also directly integrated with an Android library dependency that contains common functions that are frequently used by Android developers. Testing result shows that this system saves 42% of Android application time development and generates code that has an 81% maintainability level.